THE INFLUENCE OF PERFORMANCE EXPECTANCY AND EFFORT EXPECTANCY ON QRIS BEHAVIORAL INTENTION IN COFFEE SHOPS IN MEDAN CITY - Assyifa Yasmien; Ade Indah Sari; Alvin Fahlevi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The use of information technology is inextricably linked to the use of the internet, one of the key needs for conducting financial transactions (financial technology), as evidenced by the emergence of digital wallets. Furthermore, technological advancements have also led to an increase in the number of financial service providers offering services through applications that facilitate access to financial transactions. The use of QRIS has recently become a positive trend for both users and businesses. Given its benefits in facilitating more efficient cashless transactions, the use of QRIS by MSMEs will help improve their business performance. This study aims to analyze the effect of performance expectancy and effort expectancy on behavioral intention in Coffee Shop consumers in Medan City. The population in this study is 100 customers and samples in this study using the Sampling Technique of Hair Method. The analysis technique used is multiple linear regression. The results showed that performance expectancy had a positive and significant effect on behavioral intention. Effort expectancy has a positive and significant effect on behavioral intention. Simultaneously showing that Performance Expectancy and Effort Expectancy have a significant effect on behavioral intention in Coffee Shop consumers in Medan City.